The relationality of parts for narrative identity constitution in the corporate profile translations of China’s multinational corporations - Wang, Li; Ang, Lay Hoon; Gao, Fumeng; Abdul Halim, Hazlina (Springer Nature, 2023)
The corporate profile translations of multinational corporations (MNCs) in emerging economies such as China possess rich information for narrative analysis. Nevertheless, how the parts of a corporate profile translation form a whole narrative remains undertheorized. This study, therefore, examines the relationality of parts in the corporate profile translations of China’s MNCs by integrating William Labov’s narrative structure with Margaret Somers’ narrative identity theory. Specifically, we conduct a theoretical thematic analysis of how constituents form a whole narrative in relevant corporate profiles, of the shifts in the relationality of parts from the Chinese source texts (STs) to the English target texts (TTs) of these profiles, and of the influences of these shifts on the constitution of corporate identities in the target texts. Our results show that in the corporate profiles of Chinese MNCs, episodes are not randomly selected and related to each other but follow predominant patterns. However, we find no unified patterns in the shifts in the relationality of parts via the corporate profile translation of China’s MNCs. We thus reveal how corporations’ identities are constituted in diverse ways that reflect their fluid and unique features. Accordingly, our findings have implications for translation studies and corporate communications.